Interpreting the space characteristics of everyday heritage gardens of Suzhou, China, through a space syntax approach - Kun Liu; Yunda Wang; Ruochen Yang; Zheng Xian; Shiro Takeda; Junhua Zhang; Shutang Xing (Journal of Asian Architecture and Building Engineering)
China’s everyday heritage gardens, epitomizing social and spatial logic through classical layouts, offer a window into the nexus between Chinese culture and spatial design. Using space syntax and statistical methods, we examined 27 such gardens in Suzhou, categorizing them into four groups by spatial attributes. We first quantified building spatial traits, then delved into their syntactical relationships, guiding the final clustering. Cluster A, with 17 gardens, marries architectural diversity with spatial harmony, ensuring navigability. Cluster B’s seven gardens prioritize open landscapes, minimizing buildings for clarity. Cluster C, comprising two expansive gardens, blends architectural variety with spatial coherence, albeit with some navigational complexity. Unique, Cluster D, solely Yi Garden, presents a rich spatial and architectural tapestry, demanding deeper visitor engagement. This work sheds light on the intertwining of garden design and spatial structures, underscoring influences like ownership and cultural milieu, suggesting broader applicability to heritage gardens.